Career Breakthroughs of Women in Intercollegiate Athletic Administration - Meg G. Hancock; Heidi Grappendorf; Janelle E. Wells; Laura J. Burton (Journal of Intercollegiate Sport, 2017)
Participation in mentoring is integral for advancement within sport organizations, particularly for women (Bower, 2009; Shaw, 2006). However, it is unclear how mentoring contributes to opportunities for career advancement or breakthroughs (e.g., opportunities for new functional roles, project oversight) (Mainiero, 1994). Therefore, the purpose of this study was to understand the role of mentoring as it pertains to career breakthroughs for women in intercollegiate athletic administration. This qualitative study included 51 focus group participants in athletic administration at NCAA-member institutions (divisions, I, II, and III). Results suggested mentoring as a critical factor in career advancement. Participants indicated having a mentor was highly desired. Mentoring relationships with someone internal and external to their respective athletic departments was important. However, there was little consensus on the benefits or drawbacks of having a mentor of the same or opposite sex. Implications and strategies for developing mentoring relationships are also discussed.